Cosmópolis: mobilidades culturais - Maria do Céu Fialho (Humanitas Supplementum, 2016)
Despite its tensions and contradictions, the various discourses on globalization hint at a desire to build a space and time for encounters between worlds and cultures, through the persistence of a dialogue that shortens the distances, but respects the differences. A considerable part of the political, cultural, urban, linguistic shape of the Western world drew inspirations and solutions from the experience of poleis and cosmopoleis of the Ancient World. On the other hand, mobility may even be perceived as a characteristic feature of Luso-Brazilian culture, from the Portuguese Discoveries and their cultural production in the early stages of Jesuit literature in Brazil, especially in José de Anchieta, down to António Vieira, Machado de Assis, Guimarães Rosa, among others. Therefore, the presence and the different hues respecting the topic of mobility and of old cosmopoleis in the reception of Classical Antiquity in Portuguese literature are as well a central theme of the volume.